A Case Study of Ideas behind Logo in Jazan City - Rana, Md Sohel; Umar, Mohammad; Yazdani, Faiz; Begum, Reshma (International Journal of Membrane Science and Technology, 2023)
There are so many distinguished brands like Apple, Adidas, McDonald’s, Hyundai, and Toyota that we frequently see them everywhere but never consider what their logos mean exactly. However, every line, curve, and color has a meaning behind it. Most of them were designed to indicate much more than simple beauty. Curious to know, the authors decided to report an empirical study that aimed at analyzing and identifying the concepts behind logos used by international brands and some local companies in an Arabic framework, especially in Jazan city. We earnestly hope that the findings of the present study will assist in redesigning the logos of various organizations. The present study critically reviews the current trend of using logos in and around Jazan City. The ultimate goal of the present study is to compile a list of rhetorical strategies employed by companies to attract clients and sell their products.